Fit Assessment Analysis on User Centric Shin Pad Design Based on Current Shin Pad Design - Mohamad Fadzli Amin, Mohamad Faris Aiqal; Helmy Mustafa El-Bakri (Progress in Engineering Application and Technology, 2024)
Using existing shin pad designs as a baseline, this study analyses fitness assessments with an emphasis on user-centric shin pad design. The purpose of the study is to assess the effectiveness of current shin pads in terms of overall performance, protection, and user comfort. The study looks at material qualities, biomechanical factors, and user input in detail to find possible areas where shin pad design might be improved. The ultimate objective is to provide knowledge that may direct the creation of shin pads that are more effective and user-friendly, catering to the unique requirements and preferences of users and athletes in a range of sports scenarios.